ANALISIS POLA PERMUKIMAN KAMPUNG PENELEH SURABAYA - Stivani Ayuning Suwarlan (Jurnal Arsitektur ARCADE, 2020)
Abstract: Settlement patterns in an area can change due to population growth and activity from year to year, thereby increasing the need for housing. The increased need for housing has caused local residents to build buildings without regard to initial land boundaries / initial house plots, so that building compaction occurs. As a result of building compaction can change the pattern of settlements and even create new patterns of settlement in the area. Knowing changes in patterns and the existence of new patterns is very necessary, especially for local governments as material for study in making regulations / policies. This case occurred in Surabaya Peneleh Village, which used to have settlements on the riverbank transformed into an area that had an elongated pattern following the street network and clustered pattern due to compaction of buildings.Keywords: settlement, settlement patterns, building compactionAbstrak: Pola permukiman pada suatu wilayah dapat mengalami perubahan yang disebabkan oleh pertumbuhan dan aktivitas penduduk dari tahun ke tahun sehingga meningkatkan kebutuhan rumah tinggal. Kebutuhan rumah yang meningkat ini menyebabkan penduduk setempat mendirikan bangunan tanpa memperhatikan batas lahan/ kavling awal, sehingga terjadilah pemadatan bangunan. Hasil dari pemadatan bangunan ini dapat merubah pola permukiman bahkan menciptakan pola permukiman baru pada wilayah tersebut. Diketahuinya perubahan pola dan keberadaan pola baru sangat diperlukan terutama bagi pemerintah setempat sebagai bahan kajian dalam pembuatan peraturan/ kebijakan. Hal ini terjadi pada Kampung Peneleh Surabaya yang awalnya hanya memiliki permukiman di pinggiran sungai bertransformasi menjadi wilayah yang memiliki pola permukiman memanjang mengikuti jaringan jalan dan pola mengelompok akibat pemadatan bangunan.Kata Kunci: permukiman, pola permukiman, pemadatan bangunan